2016
DOI: 10.1093/jrr/rrv103
|View full text |Cite
|
Sign up to set email alerts
|

Application of cell sorting for enhancing the performance of the cytokinesis-block micronucleus assay

Abstract: Among the numerous methods available to assess genotoxicity, the cytokinesis-block micronucleus (CBMN) assay is very popular due its relative simplicity and power to detect both clastogenic and aneugenic compounds. A problem with the CBMN assay is that all DNA damaging agents also inhibit the ability of cells to progress through mitosis, leading to a low number of binucleated cells (BNCs). One method to resolve this issue is to ensure a sufficient proportion of BNCs in the samples. In the current study, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In the CBMN assay, cytostatic effects are calculated by recording the proportion of mono‐, bi‐, and multinucleated cells as well as necrotic and apoptotic cell ratios (Fenech 2007). Additional optional steps can include using cell sorting techniques to increase the yield of binucleated cells for subsequent analysis (Nakamura et al 2016).…”
Section: Methods Of Detection and Analysis For Genomic Instability In...mentioning
confidence: 99%
“…In the CBMN assay, cytostatic effects are calculated by recording the proportion of mono‐, bi‐, and multinucleated cells as well as necrotic and apoptotic cell ratios (Fenech 2007). Additional optional steps can include using cell sorting techniques to increase the yield of binucleated cells for subsequent analysis (Nakamura et al 2016).…”
Section: Methods Of Detection and Analysis For Genomic Instability In...mentioning
confidence: 99%
“…Livingston et al [24] demonstrated that the relationship between the frequency of detection of micronuclei and the radiation dosage is described by a non-threshold linear function: y= 2.78x + 3.71. This formed the basis for the widespread micronucleus test [17,25], validated in ionizing radiation biodosimetry. In this test micronuclei detection serves as an indicator of the genotoxicity of different agents.…”
Section: Nuclear Anomalies Of Human Lymphocytes Micronucleimentioning
confidence: 99%